Wafer-scale growth of vertical-structured SnSe₂ nanosheets for highly sensitive, fast-response UV–Vis–NIR broadband photodetectors - Chen, Zhiyong (2022)
Owing to the strong light–matter interactions, 2D semiconducting thin films have shown their great potential in the development of high-performance ultraviolet–visible–near infrared (UV–Vis–NIR) broadband photodetectors (PDs). However, the planar 2D semiconducting thin films via conventional growth method are often in the form of isolated flakes and/or suffering from low absorption efficiency of light, which hinders the UV–Vis–NIR optoelectronics from widespread applications. Herein are reported high-performance nonplanar UV–Vis–NIR broadband PD arrays, based on wafer-scale, vertical-structured SnSe2 nanosheet arrays (NSAs) via low-temperature molecular beam epitaxy method. The vertical-structured SnSe2 NSAs possess light absorption efficiency of >90% covering the wave range from 340 to 650 nm. Benefiting from the excellent light trapping ability and uniformity of waferscaled SnSe2 NSAs as well as relatively short channel, the broadband PD arrays exhibit superior comprehensive performance. They achieve a high responsivity of 31.94 A W-1, fast speed (≈63 μs), and high uniformity. In addition, the responsivity of the broadband PD arrays is further improved via Zn-doping technique.